2019
DOI: 10.1016/j.cirp.2019.04.090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of superabrasive grinding points for the machining of hardened steel

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
(13 reference statements)
0
3
0
1
Order By: Relevance
“…This means that compared to the parameter Zmean_m, the Spk parameter was increasingly less sensitive to wear over the grinding-wheel life (Figure 7). This is a very important observation because the intensity of changes in the AS texture is the highest in the initial phase of the grinding-wheel operation [2,20,22,49,50]. In the phase of stable wear, the changes in the AS microgeometry are no longer clear and, as established, the Zmean_m parameter is able to visualize them to a greater extent than Spk parameter.…”
Section: The Selection Of Parameters Sensitive To Wear Of Grinding-wh...mentioning
confidence: 86%
“…This means that compared to the parameter Zmean_m, the Spk parameter was increasingly less sensitive to wear over the grinding-wheel life (Figure 7). This is a very important observation because the intensity of changes in the AS texture is the highest in the initial phase of the grinding-wheel operation [2,20,22,49,50]. In the phase of stable wear, the changes in the AS microgeometry are no longer clear and, as established, the Zmean_m parameter is able to visualize them to a greater extent than Spk parameter.…”
Section: The Selection Of Parameters Sensitive To Wear Of Grinding-wh...mentioning
confidence: 86%
“…Barth and Klocke [17] showed that the surface's hybrid Sdr and Sdq values and functional Spk and Vmp parameters correlate highly with measured grinding forces and temperature in resin bonded cBN grinding wheels when comparing new and worn wheels. Similarly, Bazan et al [11] reported that Vmp correlates highly with the wear of electroplated cBN wheels, while Spk has been used in the past to quantify the wear of electroplated cBN point grinding tools [12]. Additionally, from the set of height-based parameters, Sq, Ssk, and Sku performed well for grinding wheel condition monitoring but generally correlated to a lesser extent than hybrid and functional parameters [11,18].…”
Section: Introductionmentioning
confidence: 94%
“…Following the initial transient wear, where pullout and fracturing dominate, steady-state wear evolution is reached, during which attritious wear causes dulling of the abrasive grain tips and formation of smooth wear flats along with striation marks in the grinding direction, and progressively increasing number of active grains as the most protruding grains wear down [7,10]. It is reported that the wear behavior of electroplated cBN grains is highly dependent on the properties of the abrasive grade, workpiece material, and process parameters with variations in the observed active mechanisms commonly observed, such as a reduced tendency for pullout [11] or reduced fracturing in some cases [12]. However, a common feature across all earlier work is the conclusion that the surface topography of the grinding wheel changes dramatically as a result of wear [7].…”
Section: Introductionmentioning
confidence: 99%
“…也可将砂轮 形貌用树脂等材料直接复印成型保存, 留待后续观 察, 现在的复印技术几乎能够将砂轮的微观形貌完 整展现出来, 如图 7(c) [57] 所示. Li [58] 和 Hood 等 [59] 通过 在石墨片上对砂轮仿形获得砂轮磨损量. Bensaid 等 [60] 通过在宽约 1 mm 的钢片上应用仿形法来评估砂轮 的径向磨损.…”
Section: F O R R E V I E W O N L Yunclassified